Spontaneous Skin Tumor in a Companion Dwarf Rabbit - Martino, Pablo Eduardo; Gimeno, Eduardo Jorge; Netri, Cecilia María; Gonzaga, Maria Florencia; Origlia, Javier Aníbal (Acta Scientiae Veterinariae, 2017)
Background: Scarce reports have been published worldwide on primary skin tumours in pet rabbits. Trichoblastoma is a rare benign neoplasm of animals and humans derived from or reduplicating the primitive germ of embryonic follicular development; it was previously classified as a basal cell tumor, meanwhile its malignant counterpart is referred to as malignant trichoblastoma or trichoblastic carcinoma. Neoplasms of domestic animals that once were lumped into the broad histologic diagnosis of basal cell tumors have since been split into distinct entities, dependent on evidence of differentiation, although a cytologic diagnosis of basal cell tumor continues to be used indistinctly to represent the large, heterogeneous group of epidermal, trichofollicular, and adnexal skin tumors with basal cell characteristics. Hereby, it is described the morphological and immunohistochemical findings of a case of spontaneous malignant trichoblastoma on a domestic companion rabbit from South America. Case: A 4-year-old, male black dwarf rabbit (Oryctolagus cuniculus) was brought to the Veterinary College when appeared with a sudden appearance of a grayish nodular subcutaneous mass measuring 3.0 x 2.0 cm and located on left tarsal zone, during march 2014. A case of malignant trichoblastoma with a predominance of trabecular architecture was diagnosed based on morphologic and microscopic results. Fine-needle aspiration, histopathology and immunohistochemistry were performed on the ulcerated mass. The mass was sectioned and stained with hematoxylin and eosin (HE), periodic acid-Schiff (PAS) and Masson trichrome stain. Replicate serial sections from the paraffin-embedded tissue blocks were immunostained for cytokeratin (AE1/AE3), smooth muscle actin, polyclonal nestin, desmin and myoglobin, using commercial kits. Mayer’s hematoxylin solution was used as a counterstain. Negative controls were produced by substituting the primary antibody with 5% bovine serum albumin in phosphate buffered saline. To assess mitotic activity, mitoses count in 10 randomly selected high-power fields was done. Diagnoses was made in accordance with the recommendations for the histological classification of tumors of domestic animals. After surgical excision, the animal remains healthy. Discussion: Epithelial nonviral skin neoplasms are uncommon in rabbits and have been cited in sporadic case reports or few case series including basal cell tumors and squamous cell carcinomas. All these cases emphasized the need for cytologic criteria and nomenclature on rabbit tumors that better reflect potential variation in tissue differentiation. As a consequence, based on limited current knowledge, the practitioner is left to make decisions for diagnostics and therapeutics in these cases based upon current recommendations for other companion animals with adjustments for lagomorph physiology. This tumor, though variable in size (0.2 to 10 cm in diameter) in domestic animals (i.e., older dogs and cats), it most often appears as a solitary, well-circumscribed hairless mass in the skin, and occasionally ulcerated. The pathological data, that included tumor location, gross appearance, tumor size, growth pattern, cellular atypia, mitosis and immunohistochemistry studies, led to the malignant trichoblastoma diagnosis and these features concurred to those described in the literature. Increasing number of sporadic or induced tumors may be expected in pet rabbits in the veterinary clinic, as these animals have a high consideration among the people, and also they live longer (natural life span range: 5-10 years) than wild or farmed rabbits.